UPAYA ICNA (ISLAMIC CIRCLE OF NORTH AMERICA) DALAM MELAWAN ISLAMOPHOBIA DI AMERIKA SERIKAT - Fadhlia, Wentiza; Nizmi, Yusnarida Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Post 9/11, many American Muslims face Islamophobia greater than ever before. The cases of discriminations and anti-Islam or anti-Muslim acts frequently occur. It is heavily influenced by the news-reporting from some media in America. The right-wing media influence the American Publics thingking by presenting negative news about Islam and Muslims, mostly Arabian Muslims.This research focuses on the efforts of ICNA (Islamic Circle of North America) in fight against Islamophobia in America. ICNA in this case by means of mass media and communication media, both electronic or print media in order to construct the correct understanding of Islam. So, the means used by ICNA is the construction of understanding Islam through the media.Keywords: media, ICNA, construction of understanding, islamophobia